Sistem Kendali Temperatur, Kelembaban Tanah, Dan Cahaya Otomatis Menggunakan Raspberry Pi Pada Smart Greenhouse - Nasron, Nasron; Suroso, Suroso; Putri, Astriana Rahma (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2019)
Conventional greenhouse technology replaced by the development of smart greenhouses. In this greenhouse there is an automatic control system. Measured factors of plant growth can be controlled such as temperature, soil moisture and sunlight. Weather which often cannot be predicted causes these factors to interfere with plant growth. In this study a system for controlling temperature, soil moisture and light was made to suit the needs of plants. As a control method using the fuzzy method. This method is suitable to be applied to the control system. In detecting temperature using a DHT11 sensor, detection of soil moisture uses the YL-69 sensor and light detection using an LDR type sensor. Raspberry Pi is the main brain in this control system. The Raspberry used is the Raspberry Pi 3 Model B + which has better than the previous version. The fuzzy method designed is processed into the Raspberry Pi to produce fan output and water pumps. In the lighting system, the light will turn on if sunlight is less than the plant's needs. In the system created this has been going well. This control system is able to measure the degree of temperature, soil moisture level, and light, and control the system according to predetermined parameters